NON-CYCLICAL INDUSTRIAL PERFORMANCE IN INDONESIA: THE MODERATION OF AUDIT QUALITY - Hakim, Mohamad Zulman; Daniel Rahandri; Mochammad Farid Fadillah; Siti Nurhaliza; Aisyah Sholikhati; Ika Wulandini (ZILLZELL MEDIA PRIMA, 2024)
This study aims to analyze the factors of hexagon fraud in detecting financial statement fraud in non-cyclical sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022. Based on the purposive sampling method, the number of companies sampled in this study was 33 research criteria of non-cyclical companies with a total of 66 observations. The results of this study found that the element of pressure proxied by government projects had a significant effect on fraudulent financial statements. Meanwhile, financial targets, financial stability, changes in directors, ineffective monitoring, change in auditors, frequent number of CEO's pictures, political connections, state-owned enterprises, and audit opinions have no significant effect on fraudulent financial reports in non-cyclicals sector companies listed on the IDX 2020-2021.